Disciplining Devotion: Buddha Representations and Ideologies of Materiality in Sri Lankan Buddhism - Dean, Melanie (Anthropologica, 2020)
This article revisits the theologically problematic nature of representations of the Buddha (statues and pictures) that serve as focal points for meditation, devotional respect (bhaktiya) and worship (pūjā) for Sri Lankan Buddhists. It shows how Sri Lankan Buddhist institutional authorities highlight the metaphysical distance between such representations and their enlightened referent, the Buddha, by means of disciplinary technologies that maintain a physical and tactile distance between devotee and representation. While devotees do seem to avoid identification of the Buddha with his likenesses, this does not mean that they treat such representations as mere symbols. Rather, Buddha representations become understood as powerful objects – materialisations of the karmic merit (pin) and sin (pau) attendant on the histories of their devotion.